An Efficient Technique for Solving Bratu Type Equation via Wavelet Orthonormal Boubaker polynomials - Eman Hassan Ouda Alfrdji (Al-Qadisiyah Journal of Pure Science, 2021)
The aim of this research is to show the applicability of new truncated orthonormal Boubaker wavelet polynomials (OBWP's) for solving one dimensional Bratu-type equation with  numerically by the aid of iteration technique. Some numerical examples were added to show the ability of this kind of polynomials comparing with exact results using Matlab. Also illustrating graphs were added to verify the efficiency of the method.